PENGEMBANGAN MEDIA e-BOOKLET MENGENAI POLA MAKAN SEHAT DALAM UPAYA PENCEGAHAN DIABETES MELITUS TIPE 2 PADA REMAJA (SMPN 2 PAMANUKAN) - Zakiyatun Nufus, Fatimah Azzahra; Setiawan, Ridwan (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: the data on kidney disease due to DM increased to 8.5% or 853,240 people. Referring to the high number of cases and the management of DM, preventive measures are needed by providing health education, one way to provide a good understanding to adolescents is e-booklet media about healthy eating in an effort to prevent Type 2 DM. Objective: to develop e-booklet media about healthy eating in an effort to prevent Type 2 DM in adolescents that is suitable for use as a health education media. Methodology: the type of research is R&D (Research and Develop). The population is 67 7th grade students of SMPN 2 Pamanukan using the total sampling technique. Parametric statistical analysis using the wilcoxon test. Result: e-booklet media measuring 14.8 x 21 cm. Obtained a score of 88% with a very good category from Material Experts, 87% with a very decent category from Media Experts. There was an influence on the use of e-booklet media with an increase of 24.03%. Conclusion: the e-booklet media measures 14.8 x 21 cm. The media was declared very good and very worthy by experts and there was an influence on the provision of e-booklet media to teenagers at SMPN 2 Pamanukan.